Adequate fluid resuscitation decreases incidence of acute renal failure in burn patients - Soeselo, Daniel Ardian; Suparman, Etheldreda Alexandria Stephanie (Universa Medicina, 2019)
BACKGROUND Burns constitute a severe health problem in many countries. In Indonesia burns rank 4th of all trauma-related diseases and are a burden on the country’s health system. Adequate fluid resuscitation is the initial management of burns that determines the success of treatment. This study aimed to determine the relationship between adequate fluid resuscitation and incidence of acute renal failure in burn patients. METHODSA retrospective study of cross-sectional design was conducted on 30 burn patients who came to the Emergency Unit (ER) from January 2015-December 2017. Medical records were reviewed to examine the data on fluid resuscitation according to the Parkland formula and the laboratory data. Acute renal failure was defined as a creatinine level of more than 2.1 mg/dL after 7 days. Hypoalbuminemia was defined as an albumin level of less than 3.4 g/dL. Fisher’s exact test was used to analyze the data.RESULTSTwenty-two subjects received fluid resuscitation according to the Parkland formula and 8 did not. Twenty-five experienced complications such as acute renal failure (ARF) (13.3%), hypoalbuminemia (46.7%) and a combination of ARF and hypoalbuminemia (23.3%). One person died. Adequate fluid resuscitation was significantly associated with decrease incidence of ARF (p=0.015), but not significantly with hypoalbuminemia (p=0.214) and with mortality (p=0.267).CONCLUSIONAdequate fluid resuscitation decreased the incidence of ARF in burn patients. Consensus protocols for initial burn resuscitation and treatment are crucial to avoid the consequences of ARF after burn injury.